2001
DOI: 10.1096/fj.00-0372com
|View full text |Cite
|
Sign up to set email alerts
|

PECAM‐1 shedding during apoptosis generates a membrane‐anchored truncated molecule with unique signaling characteristics

Abstract: Shedding of cell surface molecules, including growth factor receptors, provides a mechanism by which cells regulate signal transduction events. Here we show that platelet-endothelial cell adhesion molecule (PECAM)-1 is shed from the endothelial cell surface during apoptosis and accumulates in the culture medium as a approximately 100 kDa soluble protein. The cleavage mediating the shedding is matrix metalloproteinase (MMP) dependent, as GM6001, a broad-spectrum MMP inhibitor, inhibits PECAM-1 accumulation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
90
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 62 publications
9
90
0
Order By: Relevance
“…(i) Active caspase-8 expression was suppressed in CD44KO cells as well as active caspase-3, and both were rescued by the expression of mouse CD44 and CD31 in CD44KO cells. These results confirmed that CD31 expression and active caspase-8 are related to each other, as we suggested in 2001 (23). Thus, the attenuated activation of caspase-8 in the absence of CD44 is related to CD31 expression.…”
Section: Cd44 Plays a Key Role In Regulating Endothelial Cell Prolifesupporting
confidence: 89%
See 2 more Smart Citations
“…(i) Active caspase-8 expression was suppressed in CD44KO cells as well as active caspase-3, and both were rescued by the expression of mouse CD44 and CD31 in CD44KO cells. These results confirmed that CD31 expression and active caspase-8 are related to each other, as we suggested in 2001 (23). Thus, the attenuated activation of caspase-8 in the absence of CD44 is related to CD31 expression.…”
Section: Cd44 Plays a Key Role In Regulating Endothelial Cell Prolifesupporting
confidence: 89%
“…These findings support the concept that CD44 mediates several of its effects in endothelia through modulation of cell junctional molecule expression (e.g. CD31 and VE-cadherin), which, in addition to its known modulation of junctional integrity, matrix metalloproteinase levels and activation, interactions with cortical membrane proteins, and selected signaling pathways, modulates proliferation and apoptosis (22)(23)(24)(25)(26)(27)(28)(29), further defining the integrated roles of CD44, VE-cadherin, and CD31 as critical regulators of vascular function.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…The floating cells represent a population of cells that are in the later stages of apoptosis and cannot be rescued from death (35). We found that after ϳ5-fold increase in the caspase activity the shedding of sCD46 was clearly detected in the immunoblots.…”
Section: Discussionmentioning
confidence: 81%
“…Activated inflammatory cells, including the endothelium, undergo active shedding of the extracellular domain of the CD31 molecule (34,35); this shedding could contribute to the loss of cell-cell adhesion (34) and to the rise in circulating soluble (s)CD31 during inflammatory diseases (35). Although a potential physiologic role of sCD31 serum levels in vivo remains to be determined, the membrane-anchored truncated protein remains capable of signaling (35); hence, the loss of the CD31 extracellular domain should not affect its ability to interfere with apoptosis.…”
Section: Discussionmentioning
confidence: 99%